The Philosophy of Value and Price. (May 2022) - Simon, Hermann
Value and price are the central hinges of a market economy. But we hardly ever link value and price to philosophy. What does philosophy have to do with value and price? Why should we look at something that is ubiquitous and mundane from a philosophical standpoint?